Ekstraksi Kurkuminoid dari Temulawak (Curcuma xanthorriza Roxb.) secara Perkolasi dengan Pelarut Etanol - Imam Paryanto; Bambang Srijanto (Fakultas Farmasi Universitas Pancasila, 2006)
A study has been carried out to find out the effect of temperature, solvent flow rate and ethanol-water solvent composition on curcuminoid content in the extract produced from the extraction process (percolation) of Curcuma xanthorriza Roxb. Experiment was designed and analysed using complete random analysis with 3 factors and 2 duplications. Observed variables were: (1) varied extraction temperatures of 35°C, 45° C and 55° C; (2) varied solvent flow rates of 40 ml/minute, 60 ml/minute and 80 ml/minute; and (3) various solvent (ethanol 96%-water) compositions of 100:0,75:25 and 50:50, respectively. The measurement of curcuminoid content in the extract was done using spectrophotometer UV-visible light with wavelength setting of 420 nm. The results of analysis statistically explained that temperature and solvent flowrate did not affect significantly on curcuminoid content in the extract, but ethanol-water (solvent) composition did significantly influence on extracted curcuminoid content each shown in F table 0.01. Therefore, the optimum result of the study showed that the higher the ethanol concentration in the solvent was, the higher the curcuminoid content in the extract became. The highest curcuminoid content of 10.7% in extract was resulted at temperature of 35° C, solvent flow rate of 40 ml/minute and ethanol: water (solvent) composition of 100:0.